Optimization of Implementation of Rapid Response Team In Emergency Management of Catastropic Diseases In The Hospital - Octavia, Nur Afni Herynati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Catastrophic diseases such as stroke, acute myocardial infarction, and sepsis are major causes of hospital mortality. Delays in managing these conditions can increase patient morbidity and mortality risks. Therefore, implementing a Rapid Response Team (RRT) is a strategic step to enhance emergency management effectiveness in hospitals. This study aims to evaluate the optimization of RRT implementation in handling catastrophic disease emergencies. The methods used include literature analysis, interviews with medical personnel, and implementation evaluation in several referral hospitals. The study results indicate that RRT success depends on factors such as medical personnel training, effective communication system integration, and supportive hospital policies. The discussion emphasizes the importance of interdepartmental coordination, the utilization of information technology, and periodic evaluations to improve the responsiveness of medical teams. In conclusion, optimizing RRT can enhance the effectiveness of emergency management for catastrophic diseases and reduce hospital mortality rates.